Pengaruh Financial Knowledge, Financial Confidence dan Learning Capacity terhadap Financial Behavior Gen Z di Kota Batam - Rosita, Tita; Wage, M. Sunarto (J-MAS (Jurnal Manajemen dan Sains), 2024)
Gen Z currently has greater access to financial information, but they face new challenges in managing their personal finances effectively. This study aims to investigate the influence of financial knowledge, financial confidence, and learning capacity on financial behavior of Gen Z individuals in Batam City. This study used purposive sampling method by distributing questionnaires to Gen Z in Sagulung sub-district, resulting in 204 respondents after rounding based on Jacob Cohen's calculation. This research uses quantitative methodology using multiple linear regression analysis conducted through SPSS 29 software. The results of multiple linear regression analysis show that financial knowledge has an influence of 13.5% on financial behavior, financial confidence has an influence of 20.4% on financial behavior and learning capacity has an influence of 85.8% on financial behavior. Findings measured using the coefficient of determination (R2) analysis, which shows that financial knowledge, financial confidence, and learning capacity can affect financial behavior by 76.0%. the results of the t test and f test show that financial knowledge, financial confidence, and learning capacity have a positive and significant effect on Financial Behavior.